Polyvinylpyrrolidone-Modified Taxifolin Liposomes Promote Liver Repair by Modulating Autophagy to Inhibit Activation of the TLR4/NF-κB Signaling Pathway - Ding, Qiteng; Liu, Wencong; Liu, Xinglong; Ding, Chuanbo; Zhao, Yingchun; Dong, Ling; Chen, Huiying; Sun, Shuwen; Zhang, Yiwen; Zhang, Jinping; Wu, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
Taxifolin (TAX) is a hepatoprotective flavanol compound, which is severely limited by poor solubility and low bioavailability. Liposomes (Lips) are used as a well-recognized drug carrier systems that improve the water solubility and bioavailability of drugs, but are easily damaged by gastric juice after oral administration, resulting in the release of drugs in the gastric juice. Therefore, it is important to find materials that modify liposomes and avoid the destruction of the liposomal phospholipid bilayer structure by the gastrointestinal environment. Taxifolin liposomes (TAX-Lips) were modified by polyvinylpyrrolidone-k30 (PVP-TAX-Lips) and manufactured using a thin-film hydration technique. Particle size (109.27 ± 0.50 nm), zeta potential (-51.12 ± 3.79 mV), polydispersity coefficient (PDI) (0.189 ± 0.007) and EE (84.7 ± 0.2%) of PVP-TAX-Lips were studied. In addition, the results of in vitro release experiments indicated that the cumulative release rates of TAX-Lips and PVP-TAX-Lips were 89.73 ± 5.18% and 65.66 ± 4.86% in the simulated gastric fluid after 24 h, respectively, while the cumulative release rates were 68.20 ± 4.98% and 55.66 ± 3.92% in the simulated intestinal fluid after 24 h, respectively. Moreover, PVP-TAX-Lips were able to reverse lipopolysaccharide and D-galactosamine (LPS/D-GalN)-induced acute liver injury (ALI) by inducing autophagy to inhibit the expression levels of the TLR4/NF-κB signaling pathway and inflammatory factors, which suggested that PVP-TAX-Lips played an important role in the prevention of ALI and also provided a promising drug delivery system for the application of TAX.